The Analysis of Aceh Law and Its Relevancy on National Law from Human Right Perspective - Muhamad Rizki Nugraha Darma Nagara; Mesy Faridah Hendiyani (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
Islamization took place before the era of colonialization in Indonesia. Based on Law Number 22 of 1999, the local government has the authority to conduct some policies and consider the demands of the majority of individuals, for instance, bind them by implementing some Sharia laws, to find the better policy for all groups of people, and do not neglect the demands of the minority. Aceh is one of the provinces which is implementing Sharia law in form of Qanun Jinayat or Aceh regional law. Even though Aceh has the right to establish Sharia law, they have to be integrated into our national law. Up until now, the implementation of the Aceh law led to big attention from the international community, especially from human right activist and scholars. It is still a fruitful discussion among scholars and politicians in Indonesia. In this paper, the author discusses the analysis regarding the relation of Canon Law or Qanun with national law as well as the explanation of the Memorandum of Understanding between the Indonesia government and with Free Aceh Movement (GAM). It results that Qanun is not following Indonesia Law from a human rights perspective.